Disrupted Spatial Organization of Cued Exogenous Attention Persists Into Adulthood in Developmental Dyslexia - Pina Rodrigues, Ana; Castelo-Branco, Miguel; van Asselen, Marieke (Frontiers in Psychology, 2021)
Purpose: Abnormal exogenous attention orienting and diffused spatial distribution of attention have been associated with reading impairment in children with developmental dyslexia. However, studies in adults have failed to replicate such relationships. The goal of the present study was to address this issue by assessing exogenous visual attention and its peripheral spatial distribution in adults with developmental dyslexia. Methods: We measured response times, accuracy and eye movements of 18 dyslexics and 19 typical readers in a cued discrimination paradigm, in which stimuli were presented at different peripheral eccentricities. Results: Results showed that adults with developmental dyslexia were slower that controls in using their mechanisms of exogenous attention orienting. Moreover, we found that while controls became slower with the increase of eccentricity, dyslexics showed an abnormal inflexion at 10º as well as similar response times at the most distant eccentricities. Finally, dyslexics show attentional facilitation deficits above 12º of eccentricity, suggesting an attentional engagement deficit at far periphery. Conclusions: Taken together, our findings indicate that, in dyslexia, the temporal deficits in orientation of attention and its abnormal peripheral spatial distribution are not restricted to childhood and persist into adulthood. Our results are, therefore, consistent with the hypothesis that the neural network underlying selective spatial attention is disrupted in dyslexia.